Autophagy in aquatic animals: mechanisms, implications, and future directions - Kawsar, Md. Abu; Adikari, Diponkor; Zhang, Yang (Frontiers in Immunology, 2025)
Autophagy, a highly conserved intracellular degradation process, is essential for maintaining cellular homeostasis, supporting development, modulating immune responses, and enhancing stress adaptation in eukaryotic organisms. In aquatic animals, growing evidence highlights the central role of autophagy in responding to diverse environmental stressors and microbial challenges-factors critical to aquaculture productivity and ecosystem health. This review synthesizes current knowledge on the regulation and function of autophagy in aquatic species, emphasizing key molecular pathways, environmental triggers such as temperature, salinity, hypoxia, and pollutants, and host responses to pathogenic infections. We explore model systems, particularly zebrafish, that have advanced our mechanistic understanding of autophagy, while also identifying gaps in research concerning economically important aquaculture species. Promising applications, including the use of autophagy modulators, probiotics, and gene-editing tools such as CRISPR/Cas9, are evaluated for their potential in disease prevention and environmental monitoring. Despite recent progress, selective autophagy pathways and species-specific regulatory mechanisms remain poorly understood. Future studies integrating high-throughput screening, multi-omics analyses, and functional genetics are essential to unlock the full potential of autophagy-based innovations for sustainable aquaculture development.